Description of four Apiotrichum and two Cutaneotrichosporon species isolated from guano samples from bat-inhabited caves in Japan. Issue 8 (17th August 2020) - Takashima, Masako; Kurakado, Sanae; Cho, Otomi; Kikuchi, Ken; Sugiyama, Junta; Sugita, Takashi
Abstract : Four new yeast species belonging to the genus Apiotrichum and two new yeast species belonging to Cutaneotrichosporon are described for strains isolated from guano samples from bat-inhabited caves in Japan. In 2005, we reported these isolates as Trichosporon species based on sequence analyses of the D1/D2 domain of large subunit (LSU) rRNA genes according to available basidiomycetous yeast classification criteria; however, to date, they have not been officially published as new species with descriptions. Their phylogenetic positions have been reanalysed based on comparison of internal transcribed spacer (ITS) region sequences (including the 5.8S rRNA gene) and the D1/D2 domain of the LSU rRNA gene with those of known species; we confirmed clear separation from previously described species. Physiological and biochemical properties of the isolates also suggest their distinctiveness. Therefore, we describe Apiotrichum akiyoshidainum (holotype JCM 12595 T ), Apiotrichum chiropterorum (JCM 12594 T ), Apiotrichum coprophilum (JCM 12596 T ), Apiotrichum otae (JCM 12593 T ), Cutaneotrichosporon cavernicola (JCM 12590 T ) and Cutaneotrichosporon middelhovenii (JCM 12592 T ) as new species. C. cavernicola showed particularly distinctive morphology including large inflated anomalous cells on the hyphae and germination from the cells, although clear clamp connections on the hyphae were not confirmed. Further study is needed to elucidate the morph of this species.